STRATEGI ORANG TUA DALAM MENDIDIK ANAK USIA DINI MENURUT AMSAL 22:6 TERHADAP PERKEMBANGAN KECERDASAN SPIRITUAL ANAK DAN IMPLIKASI BAGI ORANG PERCAYA - Sanjay Nadeak; Eva Sharon (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2022)
Spiritual intelligence is one of the important things possessed by early childhood as the nation's successor who is expected to make a positive contribution to the development of the Indonesian nation in the future. Developing spiritual intelligence needs to start from an early age as a foundation for development at the next stage. The research entitled